2010
DOI: 10.1111/j.1745-459x.2010.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perception and Preference of Bottled and Tap Water

Abstract: In order to understand consumer behavior toward drinking water, it is first necessary to determine sensory perception and liking for tap and bottled water. Nevertheless, sensory analysis of water is a challenge as drinking water is supposed to have almost no taste. Therefore, a methodology based on a perceptive sorting task was designed for that purpose. Six bottled mineral water and six types of tap water were presented to 389 consumers who had to group these samples according to their sensory similarities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 15 publications
4
24
0
2
Order By: Relevance
“…First, any flavor variations between the cold supply water and the bottled water control samples (sample item 2 and sample item 4) are reported by the panels to be below the threshold level. This is consistent with prior research on tap water and bottled water flavor comparisons [19]. Second, any flavor variations between the cold supply water and the potable hot water samples (sample item 2 and sample item 3) are also reported by the panels to be below the threshold level.…”
Section: Palatability Resultssupporting
confidence: 76%
“…First, any flavor variations between the cold supply water and the bottled water control samples (sample item 2 and sample item 4) are reported by the panels to be below the threshold level. This is consistent with prior research on tap water and bottled water flavor comparisons [19]. Second, any flavor variations between the cold supply water and the potable hot water samples (sample item 2 and sample item 3) are also reported by the panels to be below the threshold level.…”
Section: Palatability Resultssupporting
confidence: 76%
“…This result was also probably due to the presence of residual chlorine (chlorine also produced negative loadings on PC3) in the tap water samples. This clearly highlights the abilities of the highly trained panel since a recent study (Teillet et al, 2010a) showed that untrained consumers (two-thirds of them) could not discriminate between tap and bottled water samples when chlorine was allowed to disappear by natural aeration.…”
Section: Multivariate Analysismentioning
confidence: 74%
“…Two works by Devesa et al (2007), and García and Devesa (2009) about blending of a high mineralization resource of about 1000e1100 mg/L with membrane treated waters showed a gradual improvement when TDS decreased, and the best results were reached at 270e350 mg/L. In a recent study, Teillet et al (2010a) pointed out a TDS of 300e350 mg/L as preferred values.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the perception of the taste of the water was found to influence people's preference of different water types. Researchers found that most preferred water types have medium levels of mineralization and are perceived as tasteless and cooler (Teillet et al 2009). Furthermore, people who collected water at the CF perceived the price of filtered water as a lot less than the other group did.…”
Section: Discussionmentioning
confidence: 97%